Perception of professionals about patient safety in psychosocial care - Adrielle Cristina Silva Souza; Ana Lúcia Queiroz Bezerra; Camila Cardoso Caixeta; Eurides Santos Pinho; Thatianny Tanferri de Brito Paranaguá; Cristiane Chagas Teixeira
ABSTRACT Objective: To understand the professionals' perception of risks and factors related to patient safety incidents in psychosocial care. Methods: Descriptive-exploratory study, with a qualitative approach, carried out with 31 professionals in type III Psychosocial Health Care Centers, between October 2016 and April 2017. Data collection was mediated by the Experiential Learning Cycle. Content analysis was performed. Results: The professionals revealed risks and factors related to safety incidents in their daily practices, associated with the institution's physical and organizational structure, with the configuration of the clinical process, with clinical administration and organizational management. Final considerations: Continuous efforts are needed on the part of senior managers and professionals to improve the work process and organizational structure in psychosocial care, contributing to the development of the patient's autonomy and social rehabilitation, avoiding institutionalization and, especially, ensuring the safety of this type of care.